The Role of Computers in Promoting Environmental Awareness Among Secondary School Students: A Case Study in Chirang District, Assam - Dureja, Pankaj (Journal of Educational Research and Policies, 2025)
This study examines the role of computers in promoting environmental awareness in private and provincialized secondary schools within Chirang District, B. T. R. (Assam). It explores how digital tools are integrated into the educational system and assesses their effectiveness in enhancing environmental consciousness among students. The research adopts a qualitative methodology, using a structured questionnaire to gather data. Key findings indicate that while computer education is becoming more prevalent, disparities in infrastructure, teacher training, and access to technology hinder its effectiveness. This study highlights the need for improved digital literacy, better resource allocation, and increased institutional support to maximize the potential of computers in environmental education.